Refugee migration, labor demand, and local employment - Daniel Auer; Lilia Götz (Global Labor Organization (GLO), 2021)
Whether or not immigration negatively affects the labor market outcomes of natives is an ongoing debate. One of the challenges for empirical evidence is the simultaneity of supply- and demand-side effects. To isolate the demand side, we focus on recent refugees in Germany who are exogenously allocated to districts and largely excluded from the labor market. Using panel data of all German districts between 2010 and 2018 and leveraging variation in the local stock of asylum seekers, we find that 1,000 asylum seekers create 267 jobs on average in a district. This growth effect is mainly driven by a demand for additional labor in service, public administration, and social work. As a consequence, we also observe a significant reduction in the local unemployment rate when more refugees arrive. The dynamic panel data estimates are robust to various sensitivity checks and two different instrumental variable approaches. Quantifying the demand side of immigration adds to our understanding of local labor market dynamics in an increasingly mobile world.
Keywords: J21; J23; O15; R11; 330; labor demand; refugee migration; employment growth; unemployment